Digital polymerase chain reaction for detecting c-MYC copy number gain in tissue and cell-free plasma samples of colorectal cancer patients - Lee, Kyu Sang (Sci Rep, 2019)
We focused on the utility of the droplet digital polymerase chain reaction (ddPCR) for detecting c-MYC gene copy number (GCN) gain in cell-free plasma and tumor tissue of colorectal cancer (CRC) patients. c-MYC GCN status was determined using dual-color silver in situ hybridization (SISH) and ddPCR in retrospective cohort 1 (192 CRC patients) and prospective cohort 2 (64 CRC patients). In cohort 1, c-MYC GCN gain was observed in 34 (17.5%) patients by SISH, and in 7 (3.6%) patients by ddPCR. c-MYC GCN by SISH significantly correlated with ddPCR results (ρ = 0.532, P < 0.001). Although 40 cases (20.7%) showed intratumoral genetic heterogeneity, it did not cause discordance in results obtained by the two methods. c-MYC GCN gain, by both SISH and ddPCR was independently correlated with worst prognosis (P = 0.002). In cohort 2, c-MYC GCN estimation in tissue by ddPCR was also significantly associated with results obtained by SISH (ρ = 0.349, P = 0.005), but correlated with plasma ddPCR with borderline significance (ρ = 0.246, P = 0.050). Additionally, detecting c-MYC GCN gain in plasma with ddPCR might have relatively low sensitivity but high specificity. Our study suggests that ddPCR can be a useful tool for detecting c-MYC GCN gain as a potential prognostic biomarker in CRC tissue samples; however, this will need further verification in plasma samples.